Clinical and genetic profile of patients with seronegative coeliac disease: the natural history and response to gluten-free diet. Issue 1 (17th July 2017) - Dore, Maria Pina; Pes, Giovanni Mario; Dettori, Ivana; Villanacci, Vincenzo; Manca, Alessandra; Realdi, Giuseppe
Abstract : Objectives: Patients with clinical, genetic and histological features of coeliac disease (CD), but negative for serological markers, pose a significant clinical problem. The aim of this study was to outline a specific profile, and to evaluate the natural history and response to gluten-free diet (GFD) of patients with seronegative CD. Methods: p atients with duodenal mucosa damage Marsh I, II and III stages, HLA DQ2/DQ8 haplotype and clinical features suggestive of CD, but negative for CD serology, were defined as seronegative CD patients. Other common causes of duodenal mucosa damage were excluded. HLA–DR and DQ genotype/haplotype between all Marsh stages of patients with seronegative and seropositive CD were compared. Clinical features, laboratory testing and histological findings were evaluated after a GFD and a gluten rechallenge. A long follow-up period was available. Results: 48 patients fulfilled diagnostic criteria over a 4-year period. Clinical phenotype and HLA−DR and DQ frequencies between patients with seronegative and seropositive CD was similar. However, Marsh I stage was more prevalent in seronegative patients (42% vs 22%; p<0.05). After a 1-year GFD trial, clinical symptoms, histological features and laboratory testing improved in 40 patients and worsened in those who underwent a 6-months gluten challenge. Five patients with seronegative CD (25%) experienced the occurrence of autoimmune diseases during a median follow-up of 133 months (range 72–192). Conclusions: Patients with seronegative CD did not display a specific profile. They benefitted from GFD as patients with seropositive CD. Waiting for more sensitive serological markers, the diagnosis of seronegative CD remains a diagnosis of exclusion.